A promising growth promoting Meyerozyma caribbica from Solanum xanthocarpum alleviated stress in maize plants. Issue 10 (25th October 2019) - Jan, Farzana Gul; Hamayun, Muhammad; Hussain, Anwar; Iqbal, Amjad; Jan, Gul; Khan, Sumera Afzal; Khan, Hamayoon; Lee, In-Jung
Abstract: Fungal endophytes are known to secrete a large array of secondary metabolites (phenols, flavonoids, indole acetic acid (IAA) etc.) that facilitate crops under stress conditions. Considering this, a potent plant growth promoting endophyte (SXSp1) from the spines and leaves of Solanum xanthocarpum L. has been isolated. The isolated strain ably secreted high quantities of indole-3-acetic acid, phenols and flavonoids. Also, it exhibited phosphate solubilization, siderophore and had 2, 2 diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The SXSp1 also resisted the salinity stress up to 150 mM. LC/MS analysis of SXSp1 culture filtrate (CF) revealed the presence of p -hydroxyl benzoic acid, diadzein, genistien, myricetin and caffeoyl-d -glucose. Moreover, the inoculation of maize plants with SXSp1 significantly ( P =0.05) promoted the chlorophyll and carotenoid contents, root and shoot lengths, plant fresh and dry weights, catalase and peroxidase activities, proline, phenolics, flavonoids and relative water contents (RWCs) under salinity. More interestingly, SXSp1-associated plants showed lower endogenous abscisic acid (ABA) and higher endogenous IAA contents that helped the plants to resist salinity stress up to 100 mM. After sequencing, internal transcribed spacer (ITS) regions (ITS1 and ITS4) and phylogenetic analysis, the SXSp1 was identified as Meyerozyma caribbica .